Langues et langages du merveilleux dans L’Enjomineur : enjeux poétiques, historiques et narratifs - Joanna Pavlevski-Malingre (ReS Futurae)
Studying linguistic issues and their link to Supernatural in l’Enjomineur brings a better understanding of the poetic features of historic fantasy, of the way the human world and the Other World interact in these novels, and reveals Pierre Bordage’s views about French Revolution and human passions. The historical background of the narrative seems to forbid the use of made-up words and languages, and to involve other semiotic strategies in order to introduce supernatural elements. As a consequence, Pierre Bordage inserts foreign or unusual words in french language, to which he gives a new meaning, and he expresses the unuterableness of the Other World through numerous figures of analogy. The novel opposes several linguistic communities, corresponding to political and religious communities : the people of Vendée and their provincial dialect, and the followers of Mithra, speaking an inflated french. As he makes us hear these contrary voices, Pierre Bordage emphasizes the conflicts on which was built the Republic. Nonetheless, beyond these conflicts, these different languages are part of a global questionning of human language, which fails to express the true essence of beings. The language of silence spoken by the creatures of the Other World, who perceive human language as a violence which mirror unleashed human passions, is a strong condemnation of Revolution and Terror.